2011
DOI: 10.1186/1471-2156-12-84
|View full text |Cite
|
Sign up to set email alerts
|

A genetic predisposition score for muscular endophenotypes predicts the increase in aerobic power after training: the CAREGENE study

Abstract: BackgroundIt is widely accepted that genetic variability might explain a large part of the observed heterogeneity in aerobic capacity and its response to training. Significant associations between polymorphisms of different genes with muscular strength, anaerobic phenotypes and body composition have been reported. Muscular endophenotypes are positively correlated with aerobic capacity, therefore, we tested the association of polymorphisms in twelve muscular related genes on aerobic capacity and its response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 35 publications
4
45
1
Order By: Relevance
“…rs17602729 in the AMPD1 gene and rs1016732 and rs2854248 in the ATP1A2 gene showed a large overlap between the different strength phenotypes. Rs17602729 of the AMPD1 gene has previously been shown to be associated with a diminished aerobic capacity and cardiorespiratory response to exercise (22,28) and a decrease in exercise duration for 20 years (25). Likewise, markers from ATP1A2 were associated with a decrease in exercise duration (25).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…rs17602729 in the AMPD1 gene and rs1016732 and rs2854248 in the ATP1A2 gene showed a large overlap between the different strength phenotypes. Rs17602729 of the AMPD1 gene has previously been shown to be associated with a diminished aerobic capacity and cardiorespiratory response to exercise (22,28) and a decrease in exercise duration for 20 years (25). Likewise, markers from ATP1A2 were associated with a decrease in exercise duration (25).…”
Section: Discussionmentioning
confidence: 91%
“…Regular physical activity in cardiac rehabilitation improves aerobic power and skeletal muscle strength and is associated with an increase in survival in these patients (15,18,37). However, individual differences in the response to rehabilitation are large (38), which may be partly related to genetic characteristics (28).…”
mentioning
confidence: 98%
“…In a study of Rico-Sanz et al [54], subjects with the AMPD1 XX genotype had diminished exercise capacity and cardiorespiratory responses to exercise in the sedentary state. In a study of 935 Coronary artery disease patients, the carriers of the X allele had a significantly lower relative increase in peakVO 2 after 3 months of aerobic training [55]. Finally, two studies reported low frequency of the mutant X allele in a group of top-level Spanish male endurance athletes (cyclists and runners, n ¼ 104) [56] and 127 Polish rowers [57] compared with controls.…”
Section: Ampd1 Gln12 Allelementioning
confidence: 96%
“…The study involved 289 male soccer players (aged [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] …”
Section: Participantsmentioning
confidence: 99%
“…Those with a CC genotype have a normal outcome with no deficiency in the enzyme and those with a T allele have a deficiency in the AMPD1 enzyme. Deficiency in AMPD1 can cause symptoms such as pain, cramping and weakness of muscles after exercise (Sabina et al, 1984;Thomaes et al, 2011). The COL5A1 gene encodes the protein Collagen alpha-1(V) chain, which is involved in the formation of connective tissue in the musculoskeletal system.…”
Section: Introductionmentioning
confidence: 99%